Empirical model of teachers’ neuroplasticity knowledge, mindset, and epistemological belief system - Gholami, Khalil; Alikhani, Maryam; Tirri, Kirsi (Frontiers in Psychology, 2022)
Educational research has shown that teachers’ knowledge and beliefs are two important variables that significantly affect their pedagogical practice and decisions. Relying on the premise that knowledge is superior to beliefs in a pure epistemic dimension and rooted in the previous empirical studies, we examined the hypothesis that teachers’ knowledge of neuroplasticity affects their epistemological belief system mediated by mindset. Using a survey consisting of established scales about these variables, we collected data from a sample of 345 teachers. Structural equation modeling was performed to test the hypothesis. Results showed that the path coefficients (direct effects) from teachers’ knowledge of neuroplasticity to their mindset and epistemological belief system were statistically significant. In other words, we found that teachers with a higher score in the knowledge of neuroplasticity had a growth mindset and a sophisticated epistemological belief system. Teachers’ knowledge of neuroplasticity also had an indirect effect on their epistemological belief system mediated by mindset. This result has a conceptual contribution to the literature because it suggests that teachers’ knowledge of neuroplasticity is a predicting variable for mindset and epistemological belief system. In practice, it provides us with a tool for developing teachers’ growth mindset and sophisticated epistemological beliefs.